Сравнительный анализ методов визуализации в диагностике асептического некроза головки бедренной кости - Соснина, Ю. К. (ХНУРЭ, 2008)
The possibilities and comparative description of methods of visualization are considered in diagnostics of aseptic necrosis of head of thigh-bone. Development of original method of ultrasonic scan-out allowing expose this pathology on an early stage is assumed.
Keywords: диагностика асептического некроза; диагностика